Citrate carrier activity and cardiolipin level in eel (Anguilla anguilla) liver mitochondria - Giudetti A. M.; Siculella L.; Gnoni G. V. (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2002)
The activity of the tricarboxylate (citrate) carrier has been assayed in intact liver mitochondria from yellow eel (Anguilla anguilla) and compared to that from rat. The eel-citrate carrier specific activity was approximately 1.7-fold higher than that assayed in rat-liver mitochondria. The content of the main mitochondrial phospholipids, phosphatidylethanolamine and phosphatidylcholine, did not show a significant difference between the two species, while in eel a higher cardiolipin level was observed. Fatty acid composition of eel-liver mitochondrial phospholipids was characterised by a large amount of unsaturated fatty acids, dominated by octadecaenoic acid (C18:1n-9) and docosahexaenoic acid (C22:6n-3). The cardiolipin fatty acid pattern of eel-liver mitochondria showed, with respect to the rat, a higher C20:5n-3 and C22:6n-3 content and a lower amount of C18:2n-6 and C20:4n-6. A noticeable activity of lipogenic enzymes was also detected in eel liver cytosol. The results of this study suggest that the remarkable activity of the citrate carrier in eel-liver mitochondria can most likely be ascribed to a considerable cardiolipin level. A covariance of citrate carrier and lipogenic enzyme activities was observed. © 2002 Elsevier Science Inc. All rights reserved.